Circular RNAs - Dieterich, Christoph; Baudet, Marie-Laure (Springer US, 2024)
Purification of circular RNAs using poly(A) tailing followed by RNase R digestion -- State of the art circular RNA analytics using the circtools software suite -- Exploring circular RNA profile and expression in extracellular vesicles -- Sanger sequencing to determine the full-length sequence of circular RNAs -- Droplet digital PCR for the detection and quantification of bona fide circRNAs -- Targeted sequencing of circular RNAs for Illumina-based counting and Nanopore structure determination -- Nanopore mediated sequencing of circular RNA -- In vivo tissue-specific knockdown of circRNAs using shRNAs in Drosophila Melanogaster -- Functional circular RNA screening via RfxCas13d/BSJ-gRNA system -- Base-editor-mediated circRNA knockout by targeting predominantly back-splice sites -- Directed Circularization of a Short RNA -- Engineering Synthetic circRNAs for Efficient CNS Expression -- Functional investigation of in vitro transcribed circular RNA and formulation into Lipid nanoparticles via microfluidic mixing -- Characterising post-transcriptional modifications of circRNAs to investigate biogenesis and translation -- Native circular RNA pulldown method to simultaneously profile RNA and protein interactions -- Screening and characterization of functional circRNAs in neuronal cultures. .